Listening in English Classes: Learners' Perspective - Procházková, Michaela (Univerzita Pardubice, 2017)
This bachelor thesis deals with listening in English classes and the learners' perspective on the listening skill in the context of Czech elementary schools. In the theoretical part, the Framework Educational Programme for Basic Education and the foreign language section is mentioned as well as the Common European Framework of Reference for Languages, from which the communicative competences are discussed in the paper. Next, the listening skill and the different roles of listening and activities connected to listening are found in the paper. In the practical part, learners' perspective and opinions on listening are answered in the form of a questionnaire.
Pohled žáků na výuku poslechu v hodinách anglického jazyka
Keywords: poslech; poslechové aktivity; komunikační kompetence; pohled žáků; listening; listening activities; communicative competences; learners' perspective